2003
DOI: 10.1542/peds.112.4.e275
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Care in Premature Infants: The Effect of Two Different Cord-Care Regimens (Salicylic Sugar Powder vs Chlorhexidine) on Cord Separation Time and Other Outcomes

Abstract: ABSTRACT. Objectives. To evaluate the effect of 2 cord-care regimens (salicylic sugar powder vs chlorhexidine as a 4% detergent water solution) on cord separation time and other outcomes in preterm infants.Methods. A prospective, randomized, controlled trial was conducted on 244 preterm newborns with a gestational age of <34 weeks and a birth weight of <2500 g. All preterm newborns were enrolled, regardless of their health condition. We excluded from the study infants whose conditions during the first hours of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
1
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 22 publications
0
18
1
8
Order By: Relevance
“…1 Pezzati et al 5 found no significant difference in the percentages of S aureus, Streptococcus, E coli and total colonization in the alcohol, natural drying, and SSP groups. Although no neonate developed omphalitis, and the rate of omphalitis was not necessarily related to the colonization rate, 4,6,9 in this study, colonization percentages were high in the alcohol and natural drying groups. It is possible that the swab sites in the SSP group had already shown less moisture and fast withering in comparison with the other groups on the third day after birth.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…1 Pezzati et al 5 found no significant difference in the percentages of S aureus, Streptococcus, E coli and total colonization in the alcohol, natural drying, and SSP groups. Although no neonate developed omphalitis, and the rate of omphalitis was not necessarily related to the colonization rate, 4,6,9 in this study, colonization percentages were high in the alcohol and natural drying groups. It is possible that the swab sites in the SSP group had already shown less moisture and fast withering in comparison with the other groups on the third day after birth.…”
Section: Discussionmentioning
confidence: 47%
“…6 The shortest period was 2 days in this study's SSP group. This supports the conclusion that the use of powder form is more effective in Table 2 shortening cord separation time than the use of liquid form.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations